2015
DOI: 10.1371/journal.pgen.1005328
|View full text |Cite
|
Sign up to set email alerts
|

Context-Dependent Functional Divergence of the Notch Ligands DLL1 and DLL4 In Vivo

Abstract: Notch signalling is a fundamental pathway that shapes the developing embryo and sustains adult tissues by direct communication between ligand and receptor molecules on adjacent cells. Among the ligands are two Delta paralogues, DLL1 and DLL4, that are conserved in mammals and share a similar structure and sequence. They activate the Notch receptor partly in overlapping expression domains where they fulfil redundant functions in some processes (e.g. maintenance of the crypt cell progenitor pool). In other proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(59 citation statements)
references
References 96 publications
(121 reference statements)
1
55
0
Order By: Relevance
“…Notch1 and DLL1 oscillations could underlie the pulse dynamics (Bone et al, 2014; Kim et al, 2011; Liao et al, 2016; Shimojo and Kageyama, 2016). However, restoration of non-oscillatory expression of DLL1 in the mouse PSM leads to the formation of normal somites (Preusse et al, 2015). Our data suggest that in the excitable regime, Notch signaling is required both for the initiation ( i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Notch1 and DLL1 oscillations could underlie the pulse dynamics (Bone et al, 2014; Kim et al, 2011; Liao et al, 2016; Shimojo and Kageyama, 2016). However, restoration of non-oscillatory expression of DLL1 in the mouse PSM leads to the formation of normal somites (Preusse et al, 2015). Our data suggest that in the excitable regime, Notch signaling is required both for the initiation ( i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In the optic cup, Dll1 mRNA is first detectable at E10.5, just ahead of the first wave of neurons at E11.0 (Bao and Cepko, ; Rocha et al, ; Luo et al, ). By midgestation, about 80% of Dll4 + retinal cells coexpress Dll1 , suggesting that Dll1 activity starts earlier and acts more broadly (Rocha et al, ; Preusse et al, ). It further implies that Dll1 and Dll4 laterally inhibit neighboring RPCs, largely by signaling from postmitotic cells.…”
Section: Discussionmentioning
confidence: 99%
“…By comparison, Notch1 receptor mutants have a profound reduction of proliferating RPCs (Jadhav et al, 2006;Yaron et al, 2006). A recent study also showed that Dll4 substitution into the Dll1 locus fully rescued the Dll1 RPC phenotype (Preusse et al, 2015). Thus, in the early retina it seems clear that Dll1 and Dll4 redundancy reinforces the lateral inhibition signal (in trans) to neighboring Notchþ, Hes1þ RPCs.…”
Section: Maintaining the Retinal Progenitor Cell Poolmentioning
confidence: 98%
“…15,17,56 Besides, DLL4 is ~50% identical to DLL1 at the amino acid level. 57 These structure differences and the dramatic difference of amino acid sequence among Notch ligands may explain their functional differences.…”
Section: Dll4+ DC Activation Of Notch Signaling In T Cellsmentioning
confidence: 99%